Feminism and Political Islam. A One day Seminar presented by Prof Norani Othman (IKMAS-UKM) - Sharifah S., Wan Ahmad; Hew, Cheng Sim (Faculty of Social Sciences, 2014)
For almost three decades, women activists and rights groups in Muslim societies have been pushing for law and social reform to establish equality and gender rights between men and women in the institutions of marriage and the family. These law reforms intending to improve marital and family relations through reforms of existing Muslim/Islamic family laws or personal status codes were advocated by various women’s groups within the legal and constitutional framework of their respective nation-states. In most cases, the main objective of such law reform is to remove discrimination against women in relation to marriage, divorce, and child custody. Since the period of the UN Decade for Women (1975-1985) and throughout the 1990s [spurred by the UN Fourth World Conference on Women in Beijing in 1995], the agenda to promote or establish a global campaign for women’s human rights using the Platform of Action of the Beijing Conference saw the emergence and rise of a wave of transnational women advocacy movements that include Muslim women’s groups. The rise of Muslim feminist activism is situated both within this global and their own respective national contexts.